Think one team : the revolutionary 90-day plan that engages employees, connects silos and transforms organisations - Winter, Graham (John Wiley & Sons, 2016)
Inspire and empower your team to collaborate across any boundary Think One Team, 2 nd Edition: The Revolutionary 90 Day Plan that Engages Employees, Connects Silos and Transforms Organisations weaves a fascinating and entertaining tale that reveals how a simple change in approach can free your organisation of silo-based thinking, and empower your team to act as a single unit. This imaginative, yet practical text is fully revised and updated, and has been specifically designed to guide you in creating and sustaining the agile, teamwork-focused environment that is essential to thriving in a rapidly changing world. Throughout this enlightening resource, you will explore the five practices that define the difference between fragmented, silo-based groups and a team that thinks and acts as one. In the business world, when teams are not aligned and don't collaborate across the various boundaries, they put the whole organisation at risk. This irritates customers, frustrates employees and causes countless lost opportunities. Think One Team gives you the step-by-step guide to unlock the potential in your own team and to inspire others by showing them that the era of silo thinking is over. Break down old and outdated silo-based thinking habits, and replace them with nimble and effective decision-making methods Drive change through collaboration and co-creation, empowering teams to respond and adapt quickly Coach your team to think, learn and act as a single unit, rather than a fractured collection of independent professionals Leverage an online toolbox brimming with materials that reinforce lessons on how to lead and how to build and connect effective teams Think One Team, 2 nd Edition: The Revolutionary 90 Day Plan that Engages Employees, Connects Silos and Transforms Organisations is an engaging book that breaks the cycle of silo-based thinking and empowers your team to thrive in an ever-changing world.